Industrial diet intervention modulates the interplay between gut microbiota and host in semi-stray dogs - Soufien Rhimi; Amin Jablaoui; Juan Hernandez; Vincent Mariaule; Nizar Akermi; Tristan Méric; Héla Mkaouar; Magdalena Wysocka; Adam Lesner; Mohamed Ali Borgi; Emmanuelle Maguin; Moez Rhimi (Animal Microbiome)
Abstract Background The gut microbiota and derived metabolites play a key role in regulating host physiology. Diet is identified as a key regulatory factor of the microbiota composition and, potentially, of subsequent functionalities. Demonstrating the role of diet may be complex as most human studies are cross-sectional and dietary intervention is often accompanied by hygienic changes. The objective of the present study was to investigate the impact of an industrial diet on the modulation of the microbiota and targeted functionalities using a canine “natural” model. Results We carried out a controlled dietary trial in a cohort of Tunisian semi-stray dogs. We made a transition from a natural diet to an industrial kibble diet and monitored the composition of the fecal microbiota, the concentration of short-chain fatty acids (SCFA) and bile acids (BAs), and protease activities. We demonstrated that dietary change significantly decreased fecal primary bile acids levels and protease activities. Interestingly, correlation analyses demonstrated that variation of specific microbial genera were associated with modulated physiological parameters. Conclusions Our study reveals that an industrial diet induces beneficial changes in microbial composition and functions characterised by increased diversity, synthesis of SCFA and secondary bile acids production, stressing the key role of the diet-microbiota-dog crosstalk.